Association Between Interictal High-Frequency Oscillations and Slow Wave in Refractory Focal Epilepsy With Good Surgical Outcome - Ren, Guoping; Yan, Jiaqing; Sun, Yueqian; Ren, Jiechuan; Dai, Jindong; Mei, Shanshan; Li, Yunlin; Wang, Xiaofei; Yang, Xiaofeng; Wang, Qun (Frontiers in Human Neuroscience, 2020)
High frequency oscillations (HFOs) has been proposed as a promising biomarker of the epileptogenic zone (EZ). But accurate delineation of EZ based on HFOs is still challenging. Our study compared HFOs from EZ and non-EZ based on their associations with interictal slow waves, aiming at exploring a new way to localize EZ. Nineteen medically intractable epilepsy patients with good surgical outcome were included. Five-minute interictal intracranial EEG epochs of slow wave sleep were randomly selected, then ripples (80-200 Hz), fast ripples (200-500 Hz) and slow waves (0.1-4 Hz) were automatically analyzed. The EZ and non-EZ were identified by resection range during the surgeries. We found that both ripples and fast ripples superimposed more frequently on slow waves in EZ than in non-EZ (P<0.01). Although ripples preferred to occur on the down state of slow waves in both two groups, ripples in EZ tended to be closer to the down-state peak of slow wave than in non-EZ (-174 VS. -231 ms, P = 0.008). As for FR, no statistical difference was found between the two groups (P = 0.430). Additionally, slow wave containing ripples in EZ had steeper slope (1.7 VS. 1.5 uV/ms, P <0.001) and wider distribution ratio (32.3% VS. 30.1%, P <0.001) than those in the non-EZ. But for slow wave containing fast ripple, only steeper slope (1.7 VS. 1.4 uV/ms, P <0.001) was observed. Our study innovatively compared the different features of association between HFOs and slow wave in EZ and non-EZ from refractory focal epilepsy with good surgical outcome, proposing a new method to localize EZ and facilitating the surgical plan.